An examination of the relationship between motor coordination and executive functions in adolescents - Rigoli, Daniela; Piek, Jan; Kane, Robert; Oosterlaan, J. (Wiley-Blackwell Publishing Ltd., 2012)
Aim: Research suggests important links between motor coordination and executive functions. The current study examined whether motor coordination predicts working memory, inhibition, and switching performance, extending previous research by accounting for attention-deficit–hyperactivity disorder (ADHD) symptomatology and other confounding factors, in an adolescent normative sample. Method: Ninety-three adolescents (38 females, 55 males) aged 12 to 16 years (mean age 4y 2mo, SD 1y 1mo) were assessed on the Movement Assessment Battery for Children-2 (MABC-2), Wechsler Intelligence Scale for Children-IV, N-back task, the inhibition subtest from the NEPSY-II: A Developmental Neuropsychological Assessment, second edition, and the parent-rated Strengths and Weaknesses of ADHD Symptoms and Normal Behaviour Questionnaire. Results: The MABC-2 total score accounted for a significant proportion of the variance in visuospatial working memory (p=0.041) but not for verbal working memory. The MABC-2 aiming and catching component, however, was found to account for unique variance in both verbal (p=0.019) and visuospatial working memory (p=0.016). The MABC-2 total score was found to account for a significant proportion of the variance in inhibition total completion time (p=0.017). Finally, balance skills accounted for unique variance in a NEPSY-II inhibition total errors variable (p=0.020). Interpretation: The results provide support for an overlap between motor coordination and executive functions, which has important practical implications. The study also suggests shared mechanisms underpinning the relationship between these areas, including possible cerebellar involvement.